Clinical and laboratory relationships in patients with different variants of the course of systemic lupus erythematosus - V. A. Lila (Современная ревматология, 2020)
Systemic lupus erythematosus (SLE) is characterized by a variability in clinical manifestations and laboratory abnormalities, which creates objective diagnostic difficulties.Objective: to investigate clinical and laboratory parameters in patients with definite and probable SLE.Patients and methods. The investigation enrolled 94 patients, 38 of whom were diagnosed with probable SLE. All the patients underwent immunological examination and unaffected skin biopsies, followed by an immunohistochemical study, the so-called lupus strip test (LST).Results and discussion. The group of patients with definite SLE showed a direct correlation between positive LST and disease activity (r=0.6), acute skin lesion (r=0.42), and elevated anti-double-stranded DNA antibody concentrations (r=0.37), and their inverse correlation with dry syndrome (r=-0.44). In patients with probable SLE, deposition of immunoreactants in the unaffected skin was detected in almost half of the cases, despite lower disease activity and specific antibody deficiency. Thus, LST that is quite easy to use and interpret its results can be used as an additional criterion for the differential diagnosis of SLE, especially in its early stages.